A new species of Talaromyces (Trichocomaceae) from the Xisha Islands, Hainan, China - Wang, Xin-Cun; Chen, Kai; Xia, Ye-Wei; Wang, Long; Li, Tai-Hui; Zhuang, Wen-Ying (Phytotaxa, 2016)
A novel Talaromyces species was isolated from a soil sample of the Xisha Islands, Hainan, China. The culture characterization on four standardized media, microscopic observations and phylogenetic analyses based ITS, BenA and CaM regions indicate that it is new to science and named as Talaromyces xishaensis sp. nov. The new species belongs to section Talaromyces, and is related to T. cnidii, T. flavovirens and T. siamensis in the phylogeny inferred from BenA and CaM genes. It is distinguished from the latter three species by colony morphology, more metulae per verticil, subglobose to ellipsoidal conidia, and slow growth rate on CYA at 37 °C.